A promising photocathode for green hydrogen generation from sanitation water without external sacrificing agent: silver-silver oxide/poly(1H-pyrrole) dendritic nanocomposite seeded on poly-1H pyrrole film - Alnuwaiser Maha Abdallah; Rabia Mohamed (Open Physics)
A novel photocathode has shown promise for generating green hydrogen from sanitation water at a rate of 50 µmol/h per 10 cm², using waste water as an electrolyte in a three-electrode cell. This photocathode is composed of two layers: a poly(1H-pyrrole) seeding layer topped with a silver-silver oxide/poly(1H-pyrrole) (Ag-Ag2O-P1HP) dendritic nanocomposite. The nanocomposite exhibits broad light absorption up to 660 nm and possesses a bandgap of 1.8 eV. SEM images reveal that the Ag-Ag2O-P1HP nanocomposite consists of well-ordered semi-spherical nanoparticles, with an average size between 80 and 100 nm. These spherical nanoparticles offer a large surface area, which enhances photon absorption and trapping efficiency. Additionally, the crystalline structure is characterized by a small crystal size of 32 nm, further contributing to the material’s efficiency. Hydrogen generation performance was evaluated by measuring the current density (J ph) under white light and monochromatic light, compared to the dark current (J o). The photocathode’s sensitivity was tested using four different monochromatic wavelengths: 540, 440, 340, and 730 nm. The first three wavelengths – 540, 440, and 340 nm – resulted in high J ph values of −0.19, −0.20, and −0.21 mA/cm², respectively, indicating significant hydrogen production. Conversely, the 730 nm wavelength produced a lower J ph value of −0.17 mA/cm², as the energy at this wavelength is insufficient to induce significant bond vibrations, resulting in limited hydrogen production. The high efficiency, combined with the straightforward fabrication of this photocathode, suggests that it could be scaled up as a prototype for industrial hydrogen generation applications.